SURGICAL TREATMENT OPTIONS FOR CHRONIC SUBDURAL HAEMATOMA - Attiya Nasir Siddique; Shahbaz Ali Khan; Abdul Aziz Khan (Journal of Ayub Medical College Abbottabad, 2022)
Subdural hematoma is an encapsulated collection of blood under the dura matter. This commonly encountered neurosurgical disorder is best managed by surgical evacuation; however, contemporary neurosurgery lacks a consensus regarding surgical technique of choice. Due to high incidence of the condition and associated complications, vast amount of literature is available on the subject; including studies comparing efficacy of various available treatment modalities. Herein, literature on surgical techniques employed for management of Chronic Subdural Hematoma (CSDH) has been reviewed to provide an evidence-based review on best surgical practices. Following conclusions can be made on basis of evidence of various levels provided in the studied literature: (1) Twist-drill craniostomy is a relatively safe technique that can be employed under local anaesthesia, thus can be considered as first line treatment in high risk surgical candidates. (2) Single and double burr-hole craniostomies have shown comparable results. (3) Intraoperative irrigation during burr-hole craniostomy doesn’t affect outcome. (4) Drain insertion after hematoma evacuation lowers recurrence risk. (5) Position of drain is not significant but early drain removal is associated with higher recurrence rates. (6) Craniotomy is associated with high morbidity and mortality, hence should be reserved for recurrent and large septate hematoma cases. (7) Head elevation in postoperative period reduces recurrence. (8) Embolization of middle meningeal artery (EMMA): a novel treatment modality, is promising but requires further approval in terms of large sample sized multicenter randomized control trials. In conclusion further research is required on the subject to formulate guidelines regarding management of this common neurosurgical emergency.